MHD Flow of Casson Fluid Over a Porous Medium Stretching Sheet - ng, yee xuan; Noorzehan Fazahiyah Md Shab, (Enhanced Knowledge in Sciences and Technology, 2024)
This study investigates the magnetohydrodynamic (MHD) flow of a Casson fluid through a porous media stretching sheet numerically. The study considers the Casson fluid model to describe non-Newtonian behavior. The system of nonlinear ordinary differential equations is generated from the governing partial differential equations of momentum and energy conservation using the Runge-Kutta method with a shooting method. The study aims to investigate the impacts of the magnetic field parameter M, Casson fluid parameter, Prandtl number Pr, and porous medium parameter K on the velocity and thermal field profile. An increase in the magnetic parameter M values results in a decreased momentum boundary layer thickness and velocity, whereas an increase Casson fluid parameter γ values increases momentum boundary layer thickness and velocity. Furthermore, an increase in the porosity parameter K reduces the velocity profile. Greater magnetic and porous media properties correlate to higher temperature profiles. Furthermore, an increase Casson parameter γ may result in a bigger thermal boundary layer with increased thermal resistance.